Discourse Markers (DMs) of Indonesian Ya/Iya: Does It Share Similar Functions with Dutch Ja and English Yes? - Nasir, Syarif Hidayat; Tundreng, Syarifuddin; Helvira, Vivin; Kiftiah, Siti (Universitas Negeri Makassar, 2025)
Abstract. This study investigates the interactional use of Indonesian discourse markers (DMs) ya/iya, and compares their functions with their counterparts in Dutch (ja) and English (yes). While ya/iya typically signal agreement in Indonesian, this research aims to uncover the broader and more nuanced functions of these markers in spoken discourse. Employing a qualitative discourse analysis approach, the study analyzes approximately 90 minutes of naturally occurring conversation among five Indonesian international students enrolled in a Dutch language course at Radboud University Nijmegen, the Netherlands. The data were collected through audio recordings and transcribed for in-depth functional analysis. Findings reveal that ya/iya perform a range of functions beyond simple agreement, including interrupter-ya, continuer-ya, emotive-ya, and tag-ya. Some of these uses align with those documented for English yes and Dutch ja, while others demonstrate context-specific functions unique to Indonesian. The study contributes to the cross-linguistic understanding of discourse markers, highlighting their multifunctionality and pragmatics in multilingual settings. These findings offer broader implications for discourse analysis, second language pragmatics, and intercultural communication, especially in globalized educational environments where such markers mediate social interaction across languages and cultures. Keywords: Functions, discourse markers (DMs), Indonesian-ya, English-yes, Dutch-ja